Observation of nutrient uptake at the adaxial surface of leaves of tomato (Solanum lycopersicum) using Raman spectroscopy. (3rd March 2020) - Butler, Holly J.; Martin, Francis L.; Roberts, Michael R.; Adams, Steve; McAinsh, Martin R.
Abstract: Foliar application of nutrient fertilizers is standard practice in agricultural environments, and has been shown to increase crop yield and quality more efficiently and economically than soil-based fertilizers. The adsorption of macro- and micro-nutrients through the upper epidermis of leaves is largely species dependent; reliant upon penetration through the cuticle and stomata, and also upon the plant's ability to translocate the nutrient. Herein we describe a method to observe nitrate (NO3 − ) uptake at the adaxial leaf surface to determine the efficacy of foliar fertilizers. We use Raman microspectroscopy as a sensitive approach to monitor NO3 − associated vibrational modes, complemented by ion probe measurements and measurements of leaf nutrient status using flame atomic absorption spectroscopy. The results show that NO3 − uptake can be observed down to concentrations as low as 15 mM using Raman microspectroscopy over a defined surface area, and that the rate of uptake can also be quantified using this approach. These observations could also infer information regarding the transport of other ions present in nitrate salts, such as calcium (Ca), via the indirect monitoring of NO3 - specific bands. We believe that Raman microspectroscopy provides a novel method for monitoring nutrient movement throughout plant tissue, and provides a potential tool for nutrient screening.